Some factores affecting the survival of strain of a peat carrier - Randrup, Roberto Guillermo (Pesquisa Agropecuária Brasileira, 2014)
In this work, the effects of light, thickness of the polyethilene wall of the inoculant bag, inoculum, peat, and others, over the survival of the bacterias in the inoculant are studied.